2019
DOI: 10.1159/000495580
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of Natural Rubber Latex-Specific IgE in Patients Sensitized to Timothy Grass Pollen

Abstract: Background: In pollen-allergic patients, cross-reacting allergens including cross-reactive carbohydrate determinants (CCDs) and profilins may result in positive natural rubber latex (NRL)-specific IgE (sIgE) antibody tests but the relationship between this sensitization and clinical NRL type 1 allergy is poorly described. Objective: The aims of this study were to determine the frequency and clinical relevance of NRL sIgE in grass pollen-sensitized individuals and to investigate which NRL allergen components th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
5
0
4
Order By: Relevance
“…Las del tipo inmunológico se pueden subdividir en reacciones mediadas por IgE tipo I (las cuales varían mucho según la vía de exposición [cutánea, percutánea, mucosa o parenteral], la cantidad y características de los alérgenos, el nivel de sensibilización y factores propios del individuo) y reacciones mediadas por células tipo IV. 7,15 Las reacciones no inmunológicas conducen a una dermatitis de contacto irritativa con eritema, descamación y prurito, más común en las manos y en los dedos dorsales. Es una irritación inducida "mecánicamente" o por el pH alcalino de los guantes y es independiente de la composición química de estos.…”
Section: Fisiopatología Y Manifestaciones Clínicasunclassified
See 3 more Smart Citations
“…Las del tipo inmunológico se pueden subdividir en reacciones mediadas por IgE tipo I (las cuales varían mucho según la vía de exposición [cutánea, percutánea, mucosa o parenteral], la cantidad y características de los alérgenos, el nivel de sensibilización y factores propios del individuo) y reacciones mediadas por células tipo IV. 7,15 Las reacciones no inmunológicas conducen a una dermatitis de contacto irritativa con eritema, descamación y prurito, más común en las manos y en los dedos dorsales. Es una irritación inducida "mecánicamente" o por el pH alcalino de los guantes y es independiente de la composición química de estos.…”
Section: Fisiopatología Y Manifestaciones Clínicasunclassified
“…Un dato característico de esta forma de presentación es que las lesiones y los síntomas no se extienden más allá del área de la piel directamente expuesta. 15 No es necesaria la exposición previa y usualmente está relacionada con aditivos químicos durante el procesamiento del látex (carbamatos, benzotiazoles, antioxidantes y tiuram). 14 Dermatitis de contacto alérgico o hipersensibilidad tipo IV Las lesiones suelen tener bordes mal definidos y se acompañan de intenso prurito.…”
Section: Dermatitis De Contacto Irritativaunclassified
See 2 more Smart Citations
“…Consequently, a positive sIgE against crude extracts should always be interpreted with care as it might merely reflect (cross)sensitization rather than a genuine allergy. For example, for latex, it has been shown that ubiquitous structures such as α-1,3-fucose and β-1,2-xylose bearing cross-reactive carbohydrate determinants (CCD) present on glycoproteins of plants and α-1,3fucose bearing CCD of hymenoptera venom glycoproteins [14][15][16][17][18][19] and plant profilins [15][16][17][19][20][21][22][23] can elicit a false-positive latex-sIgE results. Therefore, latex-sIgE should not be used in isolation to diagnose IgE-mediated latex allergy.…”
Section: Principles Of Component Resolved Diagnosismentioning
confidence: 99%